Circular economy analysis as an element of environmentally sustainable building design - Kosmalski, Jakub; Zwarycz-Makles, Katarzyna; Kurtz-Orecka, Karolina (Instal, 2023)
The article presents a conceptual design of a single-family dwelling building that meets the current near-zero energy standard (nZEB), in which the principles of circular economy, including architectural design, selection of construction, materials and installation solutions, were taken into account in the design phase.